Remote monitoring titration clinic to implement guideline-directed therapy for heart failure patients with reduced ejection fraction: a pilot quality-improvement intervention - Romero, Erick; Yala, Stella; Sellers-Porter, Camryn; Lynch, Genevieve; Mwathi, Veronicah; Hellier, Yvette; Goldman, Svetlana; Rocha, Paulo; Fine, Jeffrey R.; Liem, David; Bidwell, Julie T.; Ebong, Imo; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Guideline-directed medical therapy (GDMT) is the recommended treatment for heart failure with reduced ejection fraction (HFrEF). However, the implementation remains limited, with suboptimal use and dosing. The study aimed to assess the feasibility and effect of a remote monitoring titration program on GDMT implementation. Methods HFrEF patients were randomly assigned to receive either usual care or a quality-improvement remote titration with remote monitoring intervention. The intervention group used wireless devices to transmit heart rate, blood pressure, and weight data daily, which were reviewed by physicians and nurses every 2–4 weeks. Medication tolerance was assessed via phone, and dosage instructions were given. This workflow was repeated until target doses were reached or further adjustments were not tolerated. A 4-GDMT score measured use and target dosage, with the primary endpoint being the score at 6 months follow-up. Results Baseline characteristics were similar (n = 55). A median of 85% of patients complied with transmitting device data every week. At the 6-month follow-up, the intervention group had a 4-GDMT score of 64.6% compared to 56.5% in the usual care group (p = 0.01), with a difference of 8.1% (95% CI: 1.7%–14.5%). Similar results were seen at the 12-month follow-up [difference 12.8% (CI: 5.0%–20.6%)]. The intervention group showed a positive trend in ejection fraction and natriuretic peptides, with no significant difference between groups. Conclusions The study suggests that a full-scale trial is feasible and that utilizing a remote titration clinic with remote monitoring has the potential to enhance the implementation of guideline-directed therapy for HFrEF.